NonPAS: A Program for Nonlinear Analysis of Flexible Pavements - Ghanizadeh, Ali Reza; Ziaie, Arash (International Journal of Integrated Engineering, 2015)
The primary step in design of a pavement using Mechanistic-Empirical (M-E) method is the analysis of pavement and calculation of the critical responses of pavement under various loadings. This confirms the need for developing pavement analysis software as an analytical base of the M-E method. To this end, NonPAS program has been developed for linear and nonlinear analysis of flexible pavements. Developed program allows nonlinear analysis of flexible pavements using five nonlinear models, including K-θ, Uzan, Uzan-Witczak, MEPDG 2002 and Bilinear models. Nonlinear Analysis of flexible pavements by utilizing these constitutive models provides a more accurate modeling of granular material behavior. Developed program can be used to analyze a pavement system consists of maximum of 10 layers, which is subjected to a maximum of six circular loads. Developed program allows for calculating the responses at 400 different points of pavement. In order to validate the results of linear and nonlinear analysis, responses obtained from NonPAS have been compared with responses obtained using Kenlayer program. Results show very good agreement between responses, which are obtained using both linear and nonlinear analysis and approve that developed program can be used with high reliability for the purposes of pavement analysis and design.